2015
DOI: 10.1002/ase.1555
|View full text |Cite
|
Sign up to set email alerts
|

VARK learning preferences and mobile anatomy software application use in pre‐clinical chiropractic students

Abstract: Ubiquitous smartphone ownership and reduced face-to-face teaching time may lead to students making greater use of mobile technologies in their learning. This is the first study to report on the prevalence of mobile gross anatomy software applications (apps) usage in pre-clinical chiropractic students and to ascertain if a relationship exists between preferred learning styles as determined by the validated VARK(©) questionnaire and use of mobile anatomy apps. The majority of the students who completed the VARK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…There is a need for students to feel sufficiently supported during their learning in order to maintain their engagement with the course. It has been well reported that students have various and often multimodal learning preferences (Meyer et al, ) and further factors such as personality (Finn et al, ) and the spatial ability of students influence successful learning of anatomy (Fernandez et al, ). Medical educators recognize the diverse learning needs of students as well as the ever‐changing learning resources students use which, most recently includes social media.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need for students to feel sufficiently supported during their learning in order to maintain their engagement with the course. It has been well reported that students have various and often multimodal learning preferences (Meyer et al, ) and further factors such as personality (Finn et al, ) and the spatial ability of students influence successful learning of anatomy (Fernandez et al, ). Medical educators recognize the diverse learning needs of students as well as the ever‐changing learning resources students use which, most recently includes social media.…”
Section: Discussionmentioning
confidence: 99%
“…Just as for game experience, this questionnaire was administered as a check on the random distribution of participants. Empirical research on the VARK questionnaire suggests that it has fair to good construct validity, but poor to moderate predictive validity (eg, Alzain, Clark, Ireson, & Jwaid, ; Fitkov‐Norris & Yeghiazarian, ; Meyer, Stomski, Innes, & Armson, ). The present study did not aim to partake in the debate on the importance of learning styles for teaching and (adaptive) learning (see Newton & Miah, ).…”
Section: Methodsmentioning
confidence: 99%
“…Many reports on student device ownership show smartphone adoption rates well above 90% (e.g. Allagui 2014;Bradley and Holley 2011;Brett 2011;Cassidy et al 2014;Meyer et al 2015), but this is not universal. Bogdanović et al (2014) reported that less than 50% of their sample owned smartphones, which became a barrier for the delivery of mobile activities.…”
Section: Costsmentioning
confidence: 99%